2019
DOI: 10.1029/2018ja026329
|View full text |Cite
|
Sign up to set email alerts
|

A Statistical Study of the Force Balance and Structure in the Flux Ropes in Mercury's Magnetotail

Abstract: This study presents a statistical investigation of the force balance and structures in the flux ropes in Mercury's magnetotail plasma sheet by using the measurements of MErcury Surface, Space ENviroment, GEochemistry, and Ranging (MESSENGER). One hundred sixty‐eight flux ropes were identified from the 14 hot seasons of MESSENGER from 11 March 2011 to 30 April 2015, and 143 of them show clear magnetic field enhancements with the core field being ≥20% higher than the background magnetic field. The investigation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

6
2

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 70 publications
0
9
0
Order By: Relevance
“…In the magnetotail lobes, more instances of magnetotail loading-unloading have been recorded postmidnight than pre-midnight (Imber and Slavin, 2017). Within the plasma sheet, dipolarizations (Sun et al, 2016;Dewey et al, 2020) and flux ropes (Sun et al, 2016;Smith et al, , 2018bZhao et al, 2019) are more abundant at dawn as measured either by event frequency or by the number of MESSENGER orbits that observed these events. As magnetotail reconnection produces these events (e.g., Slavin et al, 2012a;DiBraccio et al, 2015a;Dewey et al, 2020), their cross-tail asymmetry is indicative of the dawnside preference in Mercury's magnetotail reconnection (Sun et al, 2016;Smith et al, 2018b).…”
Section: Magnetotail Reconnection Dynamicsmentioning
confidence: 99%
“…In the magnetotail lobes, more instances of magnetotail loading-unloading have been recorded postmidnight than pre-midnight (Imber and Slavin, 2017). Within the plasma sheet, dipolarizations (Sun et al, 2016;Dewey et al, 2020) and flux ropes (Sun et al, 2016;Smith et al, , 2018bZhao et al, 2019) are more abundant at dawn as measured either by event frequency or by the number of MESSENGER orbits that observed these events. As magnetotail reconnection produces these events (e.g., Slavin et al, 2012a;DiBraccio et al, 2015a;Dewey et al, 2020), their cross-tail asymmetry is indicative of the dawnside preference in Mercury's magnetotail reconnection (Sun et al, 2016;Smith et al, 2018b).…”
Section: Magnetotail Reconnection Dynamicsmentioning
confidence: 99%
“…The magnetic flux loading‐unloading process in Mercury's magnetosphere, that is, the magnetospheric substorm, has a time scale of only 2 to 3 min (Imber & Slavin, 2017; Slavin et al, 2010; Sun et al, 2015), which is caused by the low solar wind Alfvén Mach number (Slavin & Holzer, 1979; Scurry et al, 1994) and the small magnetosphere (Siscoe et al, 1975). The low solar wind Alfvén Mach number also produces many magnetic reconnection‐generated structures in the magnetosphere, including flux transfer events near the magnetopause (Russell & Walker, 1985; Slavin et al, 2009), flux ropes (DiBraccio, Slavin, Imber, et al, 2015; Slavin et al, 2012; Sun et al, 2016; Smith et al, 2018; Zhao et al, 2019), and dipolarization fronts in the magnetotail plasma sheet (Sundberg et al, 2012; Sun et al, 2016, 2018). These magnetic structures at Mercury resemble those at Earth, but they contain strong kinetic features.…”
Section: Introductionmentioning
confidence: 99%
“…During severe solar wind conditions, Mercury's dayside magnetosphere may even disappear 13,14 . Recent observations of MESSENGER (MErcury Surface, Space ENvironment, GEochemistry, and Ranging) confirmed that Mercury's magnetosphere resembles Earth's in many aspects, such as magnetospheric structures (e.g., magnetotail, plasma mantle, and polar cusp), magnetospheric dynamic processes (e.g., flux loading-unloading, substorm dipolarizations), and magnetic structures (e.g., dipolarization fronts and flux ropes) [15][16][17][18] . However, in situ measurements to directly demonstrate the existence of Mercury's ring current are still lacking.…”
mentioning
confidence: 99%